2011
DOI: 10.1097/mop.0b013e32834618ec
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric cochlear implantation

Abstract: Cochlear implants provide sound perception to deaf children and can mitigate, to varying extents, the effects of sound deprivation on auditory development. On the basis of our understanding of brain development and language outcomes, a wider population of children are now candidates for implantation than previously considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 33 publications
0
16
0
2
Order By: Relevance
“…This was done in an effort to exclude those children who were deaf for many years and were well past the critical window for language development(8). We did not include children who did not undergo cochlear implantation because our programs do not routinely perform psychological testing on deaf children that our team members did not feel would be good candidates for cochlear implantation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was done in an effort to exclude those children who were deaf for many years and were well past the critical window for language development(8). We did not include children who did not undergo cochlear implantation because our programs do not routinely perform psychological testing on deaf children that our team members did not feel would be good candidates for cochlear implantation.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 2–3 in 1000 children are born with a significant degree of sensorineural hearing loss (78). It is estimated that about 25% of the cases of congenital hearing loss are attributed to identifiable prenatal or postnatal disease or trauma, 18% to undiagnosed genetic factors, 15% to autosomal dominant genetic mutations, 40% to autosomal recessive genetic mutations, and 2% to sex-linked genetic mutations(9).…”
Section: Introductionmentioning
confidence: 99%
“…The positive benefits of early diagnosis and cochlear implantation are well documented in the literature (Dettman et al ., 2007; Philips et al ., 2009; Ching et al ., 2009; Niparko et al ., 2010; Yoon, 2011; Geers et al ., 2011; Kral and Sharma, 2012). Parents and families have new expectations.…”
Section: Introductionmentioning
confidence: 99%
“…This seems to stand in contrast to other studies that report a greater benefit for children with early implantation over children with later interventions (7,25,26). This might be due to different reasons: first, when having a closer look at studies that reported better outcomes with earlier intervention, these often describe developmental aspects with the trajectory of aural rehabilitation.…”
Section: Discussionmentioning
confidence: 64%